Data-driven improvement of mathematics competencies in post-pandemic Colombia: Evidence from SABER 11 results and stakeholder perceptions (2021-2024) - Montero-Ojeda, Eliecer; Jaimes-Castañeda, Martha C.; Rodriguez-Mendoza, Brigitte J. (International Journal of Innovative Research and Scientific Studies, 2026)
The study investigates how data management practices can support the improvement of mathematics competencies among Colombian secondary students in the post pandemic period, focusing on evidence from SABER 11 examinations between 2021 and 2024. Using a qualitative, descriptive–interpretive design, the research combines open ended surveys with documentary analysis of official ICFES reports to identify trends, achievement gaps, influencing factors, and learning difficulties in mathematics across 18 urban and rural schools from multiple regions. The sample includes 1,125 participants (students in grades 10 and 11, university students, and mathematics teachers), allowing triangulation of perceptions with standardized test results. Data were organized through iterative categorization of responses and scores into thematic clusters related to performance levels, socio economic conditions, access to digital resources, and pedagogical practices. Results reveal persistent and, in some cases, widening gaps in mathematical performance between rural and urban schools, as well as between students from different socio economic strata, exacerbated by unequal connectivity, limited family support, and heterogeneous institutional responses during remote learning. Teachers and students report difficulties in consolidating fundamental concepts, problem solving skills, and mathematical reasoning, which align with patterns observed in SABER 11 achievement distributions. The study concludes that systematic use of assessment data, combined with context sensitive qualitative evidence, is essential to inform pedagogical and policy decisions aimed at reducing learning gaps, strengthening data literacy among school leaders and teachers, and designing targeted interventions to enhance mathematics achievement in post pandemic Colombia.